Novel Multi-Symplectic Integrators for Nonlinear Fourth-Order Schrödinger Equation with Trapped Term (Communications in Computational Physics, 2010)
The multi-symplectic Runge-Kutta (MSRK) methods and multi-symplecticFourier spectral (MSFS) methods will be employed to solve the fourth-orderSchrödinger equations with trapped term. Using the idea of split-step numericalmethod and the MSRK methods, we devise a new kind of multi-symplectic integrators,which is called split-step multi-symplectic (SSMS) methods. The numerical experimentsshow that the proposed SSMS methods are more efficient than the conventionalmulti-symplectic integrators with respect to the the numerical accuracy and conservationperserving properties.